Protective sports mouthguard. Modern materials and manufacturing methods - Zakaryan G. A. (Interactive science, 2016)
injuries during going in for sports remain a serious problem for the sports medicine and sports dentistry, in particular. In modern domestic stomatology during manufacturing of customized sports mouthguards the specialists try to use practical data obtained from the experimental studies. The aim of the experiments is to determine the optimal strength and functionality of finished products. For the production of individual splints it is necessary to take into the account various geometric parameters of the working model, based on which the necessary material is selected and the thickness of the future product is determined. The article describes the latest methods of making protective athletic mouthguards, including with the help of modern CAD/CAM systems.
Keywords: стоматология; спортивные травмы; спортивная медицина; защитные каппы; sports injury; sports medicine; protective mouthguards; dentistry